Licochalcone A Upregulates Nrf2 Antioxidant Pathway and Thereby Alleviates Acetaminophen-Induced Hepatotoxicity - Hongming Lv; Hongming Lv; Qingfei Xiao; Junfeng Zhou; Haihua Feng; Guowen Liu; Xinxin Ci (Frontiers Media S.A., 2018)
Acetaminophen (APAP) overdose-induced fatal hepatotoxicity is majorly characterized by overwhelmingly increased oxidative stress while enhanced nuclear factor-erythroid 2-related factor 2 (Nrf2) is involved in prevention of hepatotoxicity. Although Licochalcone A (Lico A) upregulates Nrf2 signaling pathway against oxidative stress-triggered cell injury, whether it could protect from APAP-induced hepatotoxicity by directly inducing Nrf2 activation is still poorly elucidated. This study aims to explore the protective effect of Lico A against APAP-induced hepatotoxicity and its underlying molecular mechanisms. Our findings indicated that Lico A effectively decreased tert-butyl hydroperoxide (t-BHP)- and APAP-stimulated cell apoptosis, mitochondrial dysfunction and reactive oxygen species generation and increased various anti-oxidative enzymes expression, which is largely dependent on upregulating Nrf2 nuclear translocation, reducing the Keap1 protein expression, and strengthening the antioxidant response element promoter activity. Meanwhile, Lico A dramatically protected against APAP-induced acute liver failure by lessening the lethality; alleviating histopathological liver changes; decreasing the alanine transaminase and aspartate aminotransferase levels, malondialdehyde formation, myeloperoxidase level and superoxide dismutase depletion, and increasing the GSH-to-GSSG ratio. Furthermore, Lico A not only significantly modulated apoptosis-related protein by increasing Bcl-2 expression, and decreasing Bax and caspase-3 cleavage expression, but also efficiently alleviated mitochondrial dysfunction by reducing c-jun N-terminal kinase phosphorylation and translocation, inhibiting Bax mitochondrial translocation, apoptosis-inducing factor and cytochrome c release. However, Lico A-inhibited APAP-induced the lethality, histopathological changes, hepatic apoptosis, and mitochondrial dysfunction in WT mice were evidently abrogated in Nrf2-/- mice. These investigations firstly implicated that Lico A has protective potential against APAP-induced hepatotoxicity which may be strongly associated with the Nrf2-mediated defense mechanisms.